Competências e habilidades em questões do Pisa : evidências na realidade do ensino de ciências em escolas de Porto Alegre e região metropolitana - Lima, Vanessa Mendes de (2018)
The following investigation aims to analyze how the skills and competencies of the PISA test questions reflect the reality of school science education in Porto Alegre and its metropolitan region. The subjects who took part in this research were three teachers from the Natural Sciences area and one hundred and nine students, aged 15 to 16 years old, from two public schools of Porto Alegre and one private school from its metropolitan region. For data collection instruments, we used questionnaires to collect their profiles; individual semi-structured interviews with teachers; semi-structured interviews in focus groups with students, and three questions, with different competencies from PISA, which were answered by the students of this research. We analyzed data collected qualitatively through Content Analysis, according to the assumptions of Bardin (2016). Analyzes compose a discussion about the proximities and disagreements between the dimensions of scientific literacy proposed by PISA and the reality of science education. In addition, they are intended to argue if the competences required by the evaluation meet scientific knowledge presented by the students taking part in this research. From the analysis of the results, it is possible to infer that the skills and competencies of the PISA questions are beyond the knowledge presented by the students; therefore, they do not reflect the reality of the science education of studied schools.